2019
DOI: 10.5489/cuaj.5836
|View full text |Cite
|
Sign up to set email alerts
|

Assessing gender trends in Canadian urology

Abstract: Introduction: The number of female medical students and physicians entering the workforce is increasing. Despite this trend, some surgical specialties are still considered male-dominant. Urology has a significant male predominance in both residency and independent practice. This male predominance could have an impact on the physician work force, mentorship opportunities for females pursuing surgery, and on medical student attraction to urology as a specialty. Research conducted in the U.S. has shown that altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…29 Documented reasons for the fewness of female urologists include but not limited to the misconception among medical students and younger doctors that urology is a male-specific specialty in addition to the paucity of potential female mentors and probably the fear of the excessive work-load and possible burn-out syndrome found among trainee urologists. 30 In our practice, there are much fewer women than males getting admission into medical schools and still much fewer enrolling into residency training in surgery. In a society still clinging much to traditional roles for the women folk, in addition to the fact that most of the urology patients are adult men, the scarcity of female urology specialists in our country is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…29 Documented reasons for the fewness of female urologists include but not limited to the misconception among medical students and younger doctors that urology is a male-specific specialty in addition to the paucity of potential female mentors and probably the fear of the excessive work-load and possible burn-out syndrome found among trainee urologists. 30 In our practice, there are much fewer women than males getting admission into medical schools and still much fewer enrolling into residency training in surgery. In a society still clinging much to traditional roles for the women folk, in addition to the fact that most of the urology patients are adult men, the scarcity of female urology specialists in our country is not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…This makes direct comparisons between surgical specialties challenging, limiting opportunities for cross-disciplinary learning between specialties. For instance, a 10-year analysis of Canadian urology residency programs using CaRMS data from 2007–2017 found no significant differences in match rate to urology by gender [ 8 ]. However, a subsequent study using CaRMS data from 2013–2019 found women less likely to match to urology [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies utilizing CaRMS data have shown differing outcomes in match results for men and women applicants. These differences can, in part, be attributed to variations in research methodologies including outcome measures, the specific surgical specialties examined, and the time periods examined in the studies [3,[8][9][10][11][12]. This makes direct comparisons between surgical specialties challenging, limiting opportunities for cross-disciplinary learning between specialties.…”
Section: Introductionmentioning
confidence: 99%